Isolasi dan karakterisasi karagenan dari rumput laut merah Kappaphycus alvarezii varietas hijau dan cokelat - Nursamsiar Nursamsiar; Anugerah Sukmayanti; Mubarak Mubarak; Andi Nur Aisyah; Megawati Megawati (Jurnal Farmasi dan Ilmu Pengobatan, 2021)
Carrageenan is a polysaccharide obtained from the extraction of red seaweed using hot water or alkaline solutions at high temperatures. Seaweed is a large commodity in South Sulawesi and is potential to be developed into a source of carrageenan. The purpose of this study was to determine the levels of carrageenan contained in red seaweed Kappaphycus alverazii. Carrageenan extraction method from red seaweed Kappaphycus alverazii green and brown varieties using gravimetric method with 96% ethanol as precipitating material which is then characterized using FTIR spectrophotometer. The results of the study showed that carrageenan levels in red seaweed Kappaphycus alvarezii green and brown varieties were 41.37% and 36.34% respectively. Carrageenan levels of green varieties are higher than brown varieties.